Synthesis and Characterization of Fullerenol using Sodium Stannite as an Electrophilic Reagent - Wang, F.F.; Li, N. (Asian Journal of Chemistry, 2012)
An electrophilic addition reaction of sodium stannite (Na2SnO2) with C60 in THF/aqueous NaOH solution can lead to the efficient synthesis of fullerenol. It is found that molecular component and yield of the fullerenol largely depend on the ratio of Na2SnO2 to C60, but less on the concentration of NaOH, as evidenced from FTIR, XPS and elemental analysis results. Samples are characterized as weak electrolyte using conductivity testing. TEM study indicates the dependence of aggregation morphology on structure of fullerenol.